Features of resistance-associated substitutions after failure of multiple direct-acting antiviral regimens for hepatitis C - Jun Itakura; Masayuki Kurosaki; Satoru Kakizaki; Keisuke Amano; Nobuaki Nakayama; Jun Inoue; Tetsu Endo; Hiroyuki Marusawa; Chitomi Hasebe; Kouji Joko; Shuichi Wada; Takehiro Akahane; et al. (JHEP Reports, 2020)
Background & Aims: We aimed to clarify the features of resistance-associated substitutions (RASs) after failure of multiple interferon (IFN)-free regimens in HCV genotype 1b infections. Methods: A total of 1,193 patients with HCV for whom direct-acting antiviral (DAA) treatment had failed were enrolled from 67 institutions in Japan. The RASs in non-structural protein (NS)3, NS5A, and NS5B were determined by population sequencing. Results: Failure of 1, 2, and 3 regimens was observed in 1,101; 80; and 12 patients, respectively. Among patients with failure of 1 regimen, Y56H and D168V in NS3 were more frequently detected after failure of paritaprevir, whereas D168E was more frequently detected after failure of regimens including asunaprevir. R30H and L31-RAS in NS5A were frequently detected after failure of regimens including daclatasvir. The prevalence of Y93-RAS was high irrespective of the regimen. S282T RAS in NS5B was detected in 3.9% of ledipasvir/sofosbuvir failures. The prevalence of D168-RAS increased significantly according to the number of failed regimens (p <0.01), which was similar to that seen with L31-RAS and Y93-RAS. The prevalence of patients with RASs in either NS3 or NS5A, or in both, increased significantly with increasing numbers of failed regimens. The P32del, which is unique to patients for whom DAA had failed, was linked to the absence of Y93H, the presence of L31F, and previous exposure to IFN plus protease inhibitor regimens. Conclusions: Failure of multiple DAA regimens can lead to the generation of multiple RASs in the NS3 and NS5A regions of the HCV 1b genome. These mutations contribute to viral resistance to multiple treatment regimens and, therefore, should be considered during decision making for treatment of chronic HCV. Lay summary: Resistance-associated substitutions (RAS) in the genome of the hepatitis C virus are 1 of the major causes for failed treatment. We investigated RASs after failure of various treatments for chronic hepatitis C, and found that more complicated RASs accumulated in the viral genome with successive failed treatments. The highly resistant P32del RAS at NS5A region was uniquely found in patients for whom DAA treatments had failed, and was linked to the presence and absence of specific RASs.